CSI512 - Data Base Management Systems February 1999 - PPSKOM, Pusat Pengajian Sains Komputer (Universiti Sains Malaysia, 1999)
UNIVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 1998/99 February 1999 CSI512 - Data Base Management Systems Duration : [3 hours] INSTRUCTION TO CANDIDATE: Please ensure that this examination paper contains FOUR questions in FIVE printed pages before you start the examination. • Answer ALL questions. • You can choose to answer either in Bahasa Malaysia or English.